Evaluation of parasitological examination, kDNA polymerase chain reaction and rK39-based immunochromatography for the diagnosis of visceral leishmaniasis in seropositive dogs from the screening-culling program in Brazil - Regina-Silva,Shara (2014)
Introduction Dogs play a primary role in the zoonotic cycle of visceral leishmaniasis (VL). Therefore, the accurate diagnosis of infected dogs, primarily asymptomatic dogs, is crucial to the efficiency of VL control programs. Methods We investigated the agreement of four diagnostic tests for canine visceral leishmaniasis (CVL): parasite detection, either after myeloculture or by direct microscopic examination of tissue imprints; kinetoplast-deoxyribonucleic acid-polymerase chain reaction (kDNA-PCR); and an immunochromatographic test (ICT). An enzyme-linked immunosorbent assay (ELISA) and an indirect immunofluorescence test (IFAT), both of which were adopted as part of the screening-culling program in Brazil, were used as reference tests. Our sample set consisted of 44 seropositive dogs, 25 of which were clinically asymptomatic and 19 were symptomatic for CVL according to ELISA-IFAT. Results The highest and lowest test co-positivities were observed for ICT (77.3%) and myeloculture (58.1%), respectively. When analyzed together, the overall percentage of co-positive tests was significantly higher for the symptomatic group compared to the asymptomatic group. However, only ICT was significantly different based on the results of a separate analysis per test for each group of dogs. The majority (93.8%) of animals exhibited at least one positive test result, with an average of 2.66 positive tests per dog. Half of the symptomatic dogs tested positive for all four tests administered. Conclusions The variability between test results reinforces the need for more efficient and reliable methods to accurately diagnose canine VL, particularly in asymptomatic animals.